SPK PENYELEKSIAN SISWA KELAS UNGGUL DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - eirlangga, Yofhanda Septi; Aldo Eko Syaputra; Muhammad Thoriq (JURNAL FASILKOM, 2024)
High-achiever classes are specialized groups comprising students who excel in two areas of assessment, possessing intelligence above the average. Teaching in these specialized classes requires specific skills to optimize the potential of the students. Each year, West Pasaman High School conducts screenings for hundreds of students eligible for placement in the high-achiever classes, which are limited to only 50 students. The selection process for these high-achiever classes at West Pasaman High School has traditionally been manual, lacking a systematic method to support the selection process. Consequently, the selection process has been time-consuming, resulting in inefficiencies, compounded by subjective factors like social jealousy over the outcomes of the selection. The proposed solution to address the issue in selecting high-achiever students is by implementing a systematic, computerized method to expedite and improve the accuracy of the selection process. The methodology employed in this study is the Analytical Hierarchy Process (AHP). The school has outlined six criteria for evaluation: normative value, adaptive value, attitude, discipline, creativity, and academic performance. The primary objective of this research conducted at West Pasaman High School is to assist the school administration in swiftly and efficiently identifying high-achiever students. The data processing from this study provides the final scores of students, ranked from highest to lowest, with the highest score obtained by 'Payau' at 0.232 or 23.2%, followed by 'Pada' with a score of 0.229 or 22.9%. It is hoped that this research can serve as a reference for the school administration in refining their selection process and identifying students deserving of a place in the high-achiever classes. Keywords: AHP, high-achiever classes, decision support system, school, selection.